CD39 as a marker of pathogenic CD8+ T cells in cancer and other chronic inflammatory diseases - Canale, Fernando Pablo (2018)
CD8+ T cells have long been considered crucial in the immune response against tumors. However, in the last decade a subpopulation of exhausted CD8+ T cells has been described which exhibit a dysfunctional phenotype and contribute to poor immune control of tumors and chronic viral infections...